Analysis of Green Sukuk Potential Against Green Infrastructure in Bekasi City - Lim Hendra; Rimi Gusliana Mais; Putri Rizky Cahyani (Journal of Economics and Business Aseanomics (JEBA), 2022)
The Republic Indonesia Government in realizing the welfare has a fundamental role that is realized through economic and infrastructure development in various cities in Indonesia. The problem faced by Indonesia in realizing this development is how to keep infrastructure development in line with efforts to preserve the environment, and this is also one of the sustainable development goals. In this study using qualitative descriptive method. Case study that uses the object of research, is City of Bekasi-West Java. Data obtained through interviews with Bekasi City Government officials, documentation and literature studies. The analysis carried out is a SWOT analysis. Based on this research, it proves that Bekasi City, when viewed from geographical aspect, regulations, and existing legal aspects, is able to issue sukuk and carry out green infrastructure development with financing from the green sukuk. However, the reality is, until now there has been no green infrastructure development in Bekasi City that uses financing sources from sukuk or green sukuk. The existing green infrastructure in Bekasi City is a project of several ministries and is not a project of Bekasi City itself.